2016
DOI: 10.1177/0310057x1604400115
|View full text |Cite
|
Sign up to set email alerts
|

Potential Donor Families' Experiences of Organ and Tissue Donation–related Communication, Processes and Outcomes

Abstract: We aimed to describe the experiences of families of potential organ and tissue donors eligible for donation after circulatory death or brain death. Forty-nine family members of potential donors from four Melbourne hospitals were interviewed to assess their experiences of communication, processes and the outcomes of donation. Interviews were recorded, transcribed verbatim and analysed thematically. Families expressed a range of perspectives on the themes of communication, hospital processes and care, the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 22 publications
2
48
0
2
Order By: Relevance
“…Many studies focus on support that assists with decision-making ( De Groot et al, 2012 ), while promoting family satisfaction is less prominent in training and assessment of outcomes ( Marck et al, 2016 ). Staff should adapt their actions to suit the family - creating opportunities for emotional expression when that is lacking, or sharing techniques (such as mindfulness) when emotions are excessive ( López Martínez et al, 2008 ; Perkins, 1987 ).…”
Section: The Family Bereavement Experiencementioning
confidence: 99%
See 4 more Smart Citations
“…Many studies focus on support that assists with decision-making ( De Groot et al, 2012 ), while promoting family satisfaction is less prominent in training and assessment of outcomes ( Marck et al, 2016 ). Staff should adapt their actions to suit the family - creating opportunities for emotional expression when that is lacking, or sharing techniques (such as mindfulness) when emotions are excessive ( López Martínez et al, 2008 ; Perkins, 1987 ).…”
Section: The Family Bereavement Experiencementioning
confidence: 99%
“…Although Ashkenazi and Cohen (2015) found that parents donating after DBD were more satisfied with the separation from their child than parents where the DCD pathway was followed, no differences were found in later adjustment ( Ashkenazi and Guttman, 2016 ). Marck et al (2016) feels that families consenting to DCD need to be well prepared for the short timeframes and possibility that organ donation may not proceed, in which case some are comforted when tissue donation is possible ( Marck et al, 2016 ; Walker and Sque, 2016 ).…”
Section: The Family Bereavement Experiencementioning
confidence: 99%
See 3 more Smart Citations